Transplantation of human neural stem cells repairs neural circuits and restores neurological function in the stroke-injured brain - Peipei Wang; Peng Liu; Yingying Ding; Guirong Zhang; Nan Wang; Xiaodong Sun; Mingyue Li; Mo Li; Xinjie Bao; Xiaowei Chen (Neural Regeneration Research)
Exogenous neural stem cell transplantation has become one of the most promising treatment methods for chronic stroke. Recent studies have shown that most ischemia-reperfusion model rats recover spontaneously after injury, which limits the ability to observe long-term behavioral recovery. Here, we used a severe stroke rat model with 150 minutes of ischemia, which produced severe behavioral deficiencies that persisted at 12 weeks, to study the therapeutic effect of neural stem cells on neural restoration in chronic stroke. Our study showed that stroke model rats treated with human neural stem cells had long-term sustained recovery of motor function, reduced infarction volume, long-term human neural stem cell survival, and improved local inflammatory environment and angiogenesis. We also demonstrated that transplanted human neural stem cells differentiated into mature neurons in vivo, formed stable functional synaptic connections with host neurons, and exhibited the electrophysiological properties of functional mature neurons, indicating that they replaced the damaged host neurons. The findings showed that human fetal-derived neural stem cells had long-term effects for neurological recovery in a model of severe stroke, which suggests that human neural stem cells-based therapy may be effective for repairing damaged neural circuits in stroke patients.